Challenges on the usability of digital platforms for informal caregivers and health professionals: the case study of Help2Care - Caroço, João (2019)
The usability of digital platforms assumes an important role in the support of health business processes. This is particularly relevant when these platforms automate previously manually-executed activities in a certain process, with the purpose of bringing time, cost and quality benefits both to end-users and health professionals. This is the main objective of the Help2Care e-Health digital platform, where informal caregivers can use a mobile app to access digital training materials on how to properly take care of their patients. Health professionals can, in turn, suggest these materials to their caregivers through a web application, communicate directly with them through a messaging system, and even perform remote health assessment and monitoring. However, the informal caregiver population presents specific attributes which, in general, require special attention for usability. Health professionals can also be challenged by such platforms and their inherent complexity. In this paper, we report the results and challenges of the usability studies performed on both mobile and web applications of the Help2Care platform.